The importance of emotional intelligence and leadership in employability - Janet, Ho Siew Ching; Daud, Yaakub; Don, Yahya (2012)
This paper will explore the importance of emotional intelligence and leadership in relation to the employability issue especially in the Malaysian cultural context.The application of emotional intelligence and leadership in the western countries can be integrated into a model of practice for Malaysia.Experts believe that no matter whether the person is an employer or an employee, there is a need to have capabilities not only in the technical area, but also soft skills such as emotional intelligence and leadership.We will discuss the importance of emotional intelligence and leadership as an added value that will lead to employability especially in the Malaysian cultural context.Some guidelines and suggestions will be given on how to capitalize on this issue to enhance employability among college community students.